Pengaruh Abamektin 18 G/L terhadap Kelimpahan Populasi dan Tingkat Serangan Thrips parvispinus Karny (Thysanoptera: Thripidae) pada Tanaman Cabai Besar - SULHAN, WAYAN AGUS ANDI; WIDANINGSIH, DWI; SUMIARTHA, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.4, Oktober 2017, 2017)
The Influence of Abamectin 18 g/l to Population Abundance and Percentage of Damage of Thirps parvispinus Karny (Thysanoptera : Thripidae) on Long Chili Papper The research was done in Kerta Village, distircts of Payangan and Gianyar Regency from December, 2016 – February 2017. This research was conducted in order to investigate the effect of 18 g/l active ingredient of Abamektin to population abundance and percentage of damage of Thrips parvispinus Karny and also crop production of long chili papper. This research used Randomized Block Design (RBD) with 5 levels of treatment and replicated five times. The result obtained from This research about The percentage of damage were moderate catagory, at 44 Days After Treatment (DAT) the highest percentage was obtained in control (38,00%) and 23,20% in treatment 1,00 ml/l. The damage percentage was affected by population abundance of T. parvispinus. The population abundance was found significantly difference between control and 1,00 ml/l treatment whics were, 11 and 4, respectively. The highest of population abundance in 51 Days After Transplanting (DAT) was 15. The plant production was also obtained significantly difference between control and treatment 1,00 ml/l were 205 g and 270 g, respectively.